Chronic periodontitis patients: Their knowledge and its correlation with oral health related quality of life - Yaacob, Munirah; Tin, Myo Han; A. Wahab, Siti Munawwarah; M. Sham, Siti Atiqah; Abllah, Zurainie (2017)
Level of periodontal diseases knowledge was evaluated among 80 chronic periodontitis (PD) patients and its correlation with patients’ self-perceive OHQoL was investigated. The Malay version of OHQoL-UK was used. Patients’ with high knowledge of PD were of severe chronic periodontitis group (p>0.05); Malay (p<0.05) and had higher economic status (p<0.05). Moreover, 50% of them who had high knowledge perceived some effects of PD on their OHQoL (p<0.05). Despite that, significant correlation but at lower strength was found between patients’ knowledge and the social aspects of OHQoL [r=0.249, p<0.05]. There were significant different in the level of PD knowledge between chronic periodontitis patients with different perception on OHQoL.